2010
DOI: 10.1108/02634501011041426
|View full text |Cite
|
Sign up to set email alerts
|

SME practice towards integrated marketing communications

Abstract: PurposeThe purpose of this paper is to discover and empirically test the gap between the theory and practice of integrated marketing communications (IMC) in small‐ and medium‐sized enterprises (SMEs).Design/methodology/approachThe paper follows a quantitative approach, using the questionnaire technique. Questionnaire items emerged from a literature review and a qualitative step (in‐depth interviews). The questionnaire was submitted to a sample of 210 manufacturing firms. Factor and cluster analysis were perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 35 publications
1
57
0
6
Order By: Relevance
“…In relation to company's annual budget a significant upwards trend for online tools can be detected, which aligns with the fact that some of the tools offered are not free of charge (online ads/banners, pay-per-click (PPC), etc.). Examining the usage of different communication tools, Gabrielli and Balboni (2010) concluded that determining the communication budget is actually the main weakness for the SMEs, because the budget is often nailed down ex post, after having fixed which kind of activities the firm intends to implement. Also, the SM usage is significantly associated to the size of marketing department, and the rationale behind this result is: more marketing personnel could potentially maintain the company's presence on more applications/platforms, build the image of corporate transparency, interact with customers, and create an authentic online brand.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In relation to company's annual budget a significant upwards trend for online tools can be detected, which aligns with the fact that some of the tools offered are not free of charge (online ads/banners, pay-per-click (PPC), etc.). Examining the usage of different communication tools, Gabrielli and Balboni (2010) concluded that determining the communication budget is actually the main weakness for the SMEs, because the budget is often nailed down ex post, after having fixed which kind of activities the firm intends to implement. Also, the SM usage is significantly associated to the size of marketing department, and the rationale behind this result is: more marketing personnel could potentially maintain the company's presence on more applications/platforms, build the image of corporate transparency, interact with customers, and create an authentic online brand.…”
Section: Discussionmentioning
confidence: 99%
“…In the same spirit, Boeck, Bendavid, and Lefebvre (2009) developed an adaptation model of how SMEs adjust their own strategies in the B2B (business-to-business) online environment. The SMEs size is found to be an important factor for wider usage of different communication tools (Gabrielli & Balboni, 2010). On a large scale, the number of employees is positively associated with the level of innovation in the company (Kaufmann, Tsangar, & Vrontis, 2012).…”
Section: Summary On Sme's Technology Adoptionmentioning
confidence: 99%
“…The lack of human resources, time and expertise are the largest barriers to digital marketing usage in the industrial context among both SMEs and larger corporations (Järvinen et al, 2012; see also Michaelidou et al, 2011). In the same vein, the skills of the employees to utilize the channels have been identified as a significant enabler of (or barrier to) adoption of digital channels in SMEs (Chen and McQueen, 2008;Gabrielli and Balboni, 2010;Sayre et al, 2012) A lack of financial resources/capital is typically considered a barrier to the growth of SMEs (Cooper et al, 1994;Federico et al, 2012;Gilbert et al, 2006) and thus also to act as a barrier to the adoption and use of digital channels. Although digital marketing, at its best, has n o v a ri ab l e c os ts , th e f i x e d c os ts m ay s ti l l b e p r oh i b i ti v e f or m an y c om p an i es .…”
Section: Resource-related Factorsmentioning
confidence: 99%
“…It is logical to argue that small firms also have limited resources for marketing programs (Gabrielli and Balboni, 2010;Reijonen, 2010). More often than not, small firms with limited resources tend to shy away from advertising and would rather rely on other informal means of marketing (Gabrielli and Balboni, 2010). As a proxy for firm resources, advertising budget is an indicator that the firm has the necessary resources to support ''non-essential'' business initiatives with no immediate financial returns such as those activities related to ESO.…”
Section: Advertising Budgetmentioning
confidence: 99%